2012
DOI: 10.1371/journal.ppat.1002825
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Co-opts Host Cells It Does Not Invade

Abstract: Like many intracellular microbes, the protozoan parasite Toxoplasma gondii injects effector proteins into cells it invades. One group of these effector proteins is injected from specialized organelles called the rhoptries, which have previously been described to discharge their contents only during successful invasion of a host cell. In this report, using several reporter systems, we show that in vitro the parasite injects rhoptry proteins into cells it does not productively invade and that the rhoptry effecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
183
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(194 citation statements)
references
References 41 publications
7
183
0
1
Order By: Relevance
“…In addition, pSTAT6 nuclear translocation, which is dependent on ROP16, can be observed in vitro and in vivo in a percentage of uninfected cells, consistent with the idea that multiple rhoptry proteins are entering these uninfected cells (105). Importantly, rhoptry secretion into uninfected cells appears to be a widespread phenomenon and can be observed in diverse types of immune and nonimmune cells (105).…”
Section: Toxoplasma Modulation Of Uninfected Cells: Is the Parasite Ssupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, pSTAT6 nuclear translocation, which is dependent on ROP16, can be observed in vitro and in vivo in a percentage of uninfected cells, consistent with the idea that multiple rhoptry proteins are entering these uninfected cells (105). Importantly, rhoptry secretion into uninfected cells appears to be a widespread phenomenon and can be observed in diverse types of immune and nonimmune cells (105).…”
Section: Toxoplasma Modulation Of Uninfected Cells: Is the Parasite Ssupporting
confidence: 63%
“…Using these Toxoplasma-Cre parasites to infect reporter cells that express only a green fluorescent protein (GFP) after Cre excises a stop codon, GFP could be detected in both infected and uninfected cells (104). In addition, pSTAT6 nuclear translocation, which is dependent on ROP16, can be observed in vitro and in vivo in a percentage of uninfected cells, consistent with the idea that multiple rhoptry proteins are entering these uninfected cells (105). Importantly, rhoptry secretion into uninfected cells appears to be a widespread phenomenon and can be observed in diverse types of immune and nonimmune cells (105).…”
Section: Toxoplasma Modulation Of Uninfected Cells: Is the Parasite Ssupporting
confidence: 61%
“…Therefore, actively invaded cells will display both RFP and GFP fluorescence, whereas cells that have phagocytosed parasites or that were invaded relatively recently will display only RFP fluorescence. Cells displaying only GFP fluorescence are thought to result from parasites injecting proteins into cells that they do not subsequently invade (33). Using this model, we demonstrated that ∼2% of lamina propria neutrophils, compared with <0.1% of other CD45 + cells, expressed GFP and therefore were actively invaded by T. gondii (Fig.…”
Section: Significancementioning
confidence: 88%
“…T. gondii can inject effector proteins into the host cell cytosol that activate the host cell transcription factors STAT3 and STAT6, two transcription factors associated with inhibition of IL-12 (36)(37)(38)(39). In addition, recent in vitro and in vivo studies that used parasites that inject Cre recombinase along with their normal cargo of rhoptry proteins (Toxoplasma-Cre parasites) combined with Ai6 mice bearing the Cre-dependent reporter (ZsGreen1 fluorescent protein) (40) revealed that the injection of rhoptry proteins into bystander cells (or multiple cells by serial injection) without invasion is one mechanism that results in a population previously designated uninfected-injected (U-I) cells (36,41,42). These previous studies indicated that U-I cells could also result from division of infected cells or from infected cells activated to kill and clear the intracellular parasite (41), and this study classifies all cells that are subject to these host-parasite interactions as U-I cells.…”
mentioning
confidence: 99%